Effectiveness of an Inpatient Movement Disorders Program for Patients with Atypical Parkinsonism - Anna D. Hohler; Jyeming M. Tsao; Douglas I. Katz; T. Joy DiPiero; Christina L. Hehl; Alissa Leonard; Valerie Allen; Maura Gardner; Heidi Phenix; Marie Saint-Hilaire; Terry Ellis (Parkinson's Disease)
This paper investigated the effectiveness of an inpatient movement disorders program for patients with atypical parkinsonism, who typically respond poorly to pharmacologic intervention and are challenging to rehabilitate as outpatients. Ninety-one patients with atypical parkinsonism participated in an inpatient movement disorders program. Patients received physical, occupational, and speech therapy for 3 hours/day, 5 to 7 days/week, and pharmacologic adjustments based on daily observation and data. Differences between admission and discharge scores were analyzed for the functional independence measure (FIM), timed up and go test (TUG), two-minute walk test (TMW), Berg balance scale (BBS) and finger tapping test (FT), and all showed significant improvement on discharge (𝑃>.001). Clinically significant improvements in total FIM score were evident in 74% of the patients. Results were similar for ten patients whose medications were not adjusted. Patients with atypical parkinsonism benefit from an inpatient interdisciplinary movement disorders program to improve functional status.